2021
DOI: 10.1002/jpen.2079
|View full text |Cite
|
Sign up to set email alerts
|

Timing of parenteral nutrition is associated with adequacy of nutrient delivery and anthropometry in critically ill children: A single‐center study

Abstract: Background The optimal timing of supplemental parenteral nutrition (PN) use in the pediatric intensive care unit (ICU) is unclear. We aimed to describe patterns of PN use in the ICU and the association between the timing of PN initiation and macronutrient delivery and anthropometry. Methods We enrolled patients (aged <18 years) with an ICU stay >3 days were started on PN in the ICU. Initiation within 48 hours of admission was deemed as early, and duration <5 days was deemed as short. We used multivariable anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The rate of infections, duration of mechanical ventilation and the length of stay in the intensive care unit were significantly lower in the late parenteral nutrition cohort (32,33). In a study evaluating nutritional status in 95 critically ill patients, the rate of parenteral nutrition was 7.7% and early parenteral nutrition was initiated in 33% of the patients in a mean duration of four days (1-6 days) (34).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of infections, duration of mechanical ventilation and the length of stay in the intensive care unit were significantly lower in the late parenteral nutrition cohort (32,33). In a study evaluating nutritional status in 95 critically ill patients, the rate of parenteral nutrition was 7.7% and early parenteral nutrition was initiated in 33% of the patients in a mean duration of four days (1-6 days) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although changes in PN initiation before and after the change in practice were clinically and statistically significant, a much larger population may be necessary to demonstrate clinical outcome differences. A single‐center prospective study of PN initiation in the PICU including 95 children showed median time to PN initiation was 4 days 53 . Investigators found 33% of patients received early PN defined as within 48 h from admission to the PICU.…”
Section: Timing Of Pn Initiation When En Is Contraindicatedmentioning
confidence: 99%
“…A single-center prospective study of PN initiation in the PICU including 95 children showed median time to PN initiation was 4 days. 53 Investigators found 33% of patients received early PN defined as within 48 h from admission to the PICU. Median PN duration was 8 days, and in 16.8% of children, PN was given for a short duration specified as <5 days.…”
Section: Referencementioning
confidence: 99%